Eficacia del programa VIVIFRAIL en la prevención de caídas en adultos mayores con deterioro cognitivo en el Centro Diurno Gerontológico Sagi Quito – Ecuador, periodo octubre 2024 – marzo 2025. - Maigua Olivo, Stephany Gianella (2025)
The aging population has led to an increased prevalence of cognitive impairment in older adults, significantly raising the risk of falls, one of the leading causes of morbidity and mortality in this demographic. This study aims to evaluate the relationship between the implementation of the vivifrail program and fall prevention in older adults with cognitive impairment attending the SAGI Day Care Center for Older Adults in Quito. The methodology follows Prospective observational design, with an intervention group participating in the vivifrail program, focused on exercises for strength, balance, and endurance, and a control group receiving conventional treatment. Assessments will include validated tools such as the Short Physical Performance Battery (SPPB) and specific scales to measure fall risk, functionality, and cognitive capacity. Data will be analyzed to determine significant differences between the groups in terms of muscle strength, balance, and fall frequency. This study seeks to highlight the importance of structured physical exercise in promoting functional autonomy and reducing fall-related complications in older adults. The expected results will contribute to the development of evidence-based geriatric physiotherapy programs, improving the quality of life for this vulnerable population.